The influence of climate change, technological progress and political change on agricultural land use: calculated scenarios for the Upper Danube catchment area - Martin Henseler; Alexander Wirsig; Tatjana Krimly; Stephan Dabbert (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
Both climate and agricultural policy changes are commonly seen as important drivers for agricultural production. In this study, scena-rios of climate and political change were calculated for the Upper Danube catchment area using the regional optimization model ACRE. Two political scenarios were calculated for the year 2020. One scenario assumes the continuation of the Common Agricultural Policy reform 2003 the other assumes a strong shift away from payments of the first pillar to payments of the second pillar of the CAP. Both scenarios were combined with four different scenarios of climate change and technological progress derived from ICCP SRES assumptions and the ACCELERATES project. The results of the scenario calculations were analysed with respect to their implica-tions for the whole catchment area as well as for selected districts. Climate change and technological progress both cause small changes in agricultural land use: fodder crop area tends to be converted to cash crop area, and intensive grasslands tend to be converted into extensive grasslands. Climate change and technological progress increase crop productivity, and consequently, total gross margin increases. The impact of climate change might get stronger toward the end of the century which is beyond the scope of the investigations presented here. The impact of climate change might thus switch from bringing net benefits in the short to medium term to bringing net losses for the area investigated in the long run.
Keywords: 330; Klimawandel; Technischer Fortschritt; Agrarpolitik; Agrarboden; Szenariotechnik; Deutschland; Österreich; Europa